Editor's invitational series: Human behavior as the warming of earth accelerates. (1st September 2014) - Foo, Koong Hean
Abstract : I have welcomed comment from our Editorial Board and other experts on this topic, consistent with a major focus of our journal. First comment received is from Koong Hean Foo, PhD (Psych, NZ); PGD (CBT, NZ), Psychology Lecturer, James Cook University, Australia at JCU Singapore, which follows below. -Robert F. Morgan, Editor